Estudo técnico do sistema de esgotamento sanitário de Itacajá - TO - Barros, Bruno Ferronato (Universidade Federal do Tocantins, 2022)
The lack of an adequate sanitary sewage collection and treatment system causes environmental and public health problems that inconvenience the population and public administrators. Another important reason to treat sewage is the preservation of the environment, avoiding the contamination of the soil, surface water, and groundwater. The instrument that makes it possible to have an adequate sanitary sewage system is the Municipal Sanitation Plan (PMSB) correlating it to the demands of the municipality. The Law 11.445/07 on Basic Sanitation presents the guidelines and its decrees present the mechanisms, tools and directives in which the basic sanitation must be in compliance. This study aimed to perform the diagnosis of the current situation and the prognosis of the future situation proposing improvements in the creation of mechanisms of public management for the municipality of Itacajá - TO. It was sought to evaluate the operation of the existing sanitary sewage system, which does not cover the entire population. Bibliographic and documental researches were used for the primary data survey, as well as field visits to the municipality. Through the diagnosis it was possible to identify that the current sanitary sewage system in the municipality is not enough to universally serve the current and future population, requiring the expansion of the sanitary sewage system. Thus, through the identification of the most relevant problems, technical alternatives for the improvement and adaptation of the existing system were suggested.